Effectiveness of Positive Psychotherapy in Improving Opiate Addicts' Quality of Life - P Porzoor; J Alizadeh Ghoradel; H Yaghuti; S Basharpoor (Drug Control Headquarters, Research and Education Office, 2016)
Objective: This study was aimed to assess the effectiveness of positive psychotherapy based on quality of life in improving opiate addicts’ quality of life. Method: A quasi experimental research design long with control group and pre-test, post-test and follow-up was employed for the conduct of this study. All the opiate addicts referring to treatment centers of Ardebil city in 2013 constituted the statistical population of the study and the number of 36 participants was selected as the sample via purposive sampling and randomly assigned into experimental and control groups. Quality-of-life-based psychotherapy was conducted on the experimental group in 8 sessions while the control group received no intervention. Quality of life questionnaire was used for data collection purposes. Results: The results suggested the effectiveness of the intervention in quality of life. Conclusion: This intervention, which is formed from the combination positive psychology and cognitive-behavioral approach, can be used as an effective treatment method.